HUBUNGAN PENGEMBANGAN KAWASAN BISNIS DAN PARIWISATA TERPADU DI KOTA MAKASSAR TERHADAP KAWASAN PESISIR KECAMATAN GALESONG UTARA KABUPATEN TAKALAR - Khairul Fuady; Fadhil Surur (UNHI Press, 2020)
Integrated business and tourism development in Makassar was an effort to utilize the potentials of the region in supporting the development activities. One of the areas that identified as having influence activities from the business and tourism area in Makassar City was North Galesong District. The area was located in the north and was approximately 27 kilometers from the capital of Takalar Regency. North Galesong District was one of the connecting routes to Akkarena Beach which was an alternative route for people from and headed to Makassar City. This study was aim to determine the relationship between the development of integrated business and tourism area in Makassar City and the coastal area in North Galesong District. Correlation analysis test was used to determine the effect of the development program. The pond, the number of fisherman, trade services and facilities, as well as road infrastructure were used as parameter. This study showed that the relationship between trade facilities and services and road infrastructure gave a positive contribution. The development of trade service activities and the increase in the length of roads were closely linked to the development of integrated business and tourism areas in Makassar City.